Breast cancer: perceptions regarding mastectomy (Research, Society and Development, 2021)
Introduction: Breast cancer presents itself through the disorganized and disordered development of cells, becoming uncontrollable and aggressive, contributing to the formation of malignant tumors. Objective: Discuss the perceptions of women facing mastectomy. Methodology: Literature review, using as research sources the Scientific Electronic Library On-line (SCIELO) and Latin American and Caribbean Literature in Health Sciences (LILACS) databases, the articles that met the inclusion criteria were selected. , which were in the publication periods from 2012 to 2021 and which have a direct relationship with the theme. Results: It was found that women with mastectomies, on the one hand, have physical difficulties with the removal of the breast, which affects their self-image, with feelings of pain, sadness and anger due to the mutilation. On the other hand, they still show feelings of hope for the support of the family and the relationship with other women who experience the same experience of mastectomy. Conclusion: Nurses can contribute through educational approaches, with a better quality of life for mastectomized patients, as well as, for the achievement of a humanized treatment, it is important to act in the preoperative and rehabilitation of women.